2012
DOI: 10.5941/myco.2012.40.4.263
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Sclerotium Rot onCymbidiumOrchids Caused bySclerotium rolfsiiin Korea

Abstract: Sclerotium rot was found on Cymbidium orchids at Seosan-si, Chungcheongnam-do, Korea, in July, 2010. Symptoms occurred on low leaves, which turned yellowish, after which the entire plant wilted. Severely infected plants were blighted and eventually died. White mycelial mats and sclerotia appeared on pseudobulbs. Based on the mycological characteristics and pathogenicity, the causal fungus was identified as Sclerotium rolfsii. This is the first report of new Sclerotium rot on Cymbidium spp. caused by S. rolfsii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…The symptoms on plants and characteristics of the species were similar to those noted in our study. S. rolfsii is also a very dangerous pathogen of orchids as described for the first time by Bag (2004) in the USA, on Cymbidium and its hybrids, and later on Phalaenopsis and Cymbidium in Korea (Han et al 2011(Han et al , 2012. Our studies also confirmed the data of Pane et al (2007) and Han et al (2012).…”
Section: Pathogenicity Testssupporting
confidence: 88%
See 1 more Smart Citation
“…The symptoms on plants and characteristics of the species were similar to those noted in our study. S. rolfsii is also a very dangerous pathogen of orchids as described for the first time by Bag (2004) in the USA, on Cymbidium and its hybrids, and later on Phalaenopsis and Cymbidium in Korea (Han et al 2011(Han et al , 2012. Our studies also confirmed the data of Pane et al (2007) and Han et al (2012).…”
Section: Pathogenicity Testssupporting
confidence: 88%
“…S. rolfsii is also a very dangerous pathogen of orchids as described for the first time by Bag (2004) in the USA, on Cymbidium and its hybrids, and later on Phalaenopsis and Cymbidium in Korea (Han et al 2011(Han et al , 2012. Our studies also confirmed the data of Pane et al (2007) and Han et al (2012). They indicated S. rolfsii as the pathogen mainly in tropical and subtropical areas or plants growing in greenhouses where 30°C was optimum for its development.…”
Section: Pathogenicity Testssupporting
confidence: 87%
“…The pathogenic fungus produces the virulence factor oxalic acid, which inhibits the host's defenses and causes stomatal opening, ultimately leading to increases transpiration rates and reduced biomass, resulting in wilting (Guimarães and Stotz, 2004;Kabbage et al, 2015). Infected plants of S. rolfsii produce white mycelial mats on the surface of the lesion, which are followed by the formation of globular nuclei either at the infection site or in the surrounding soil (Han et al, 2012;Amaradasa et al, 2020). C. oleifera is predominantly a seedling disease, and infection with S. rolfsii causes lesions to appear near the ground at the base of the stem or at the root base, which indicates a covering of white mycelium and dark-colored pycnidia.…”
Section: Current Occurrence Of Major Fungal Diseases Of Camellia Olei...mentioning
confidence: 99%
“…101 ha) of the total cultivated land for orchid production [8]. So far, the pathogens reported in Korea that cause Cymbidium disease include Fusarium subglutinans, Sclerotium rolfsii, Acidovorax avenae, Cymbidium mosaic virus and Odontoglossum ring spot virus [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%